The Impact of Spiritual Leadership and Spirit at Work as Intangible Resource Capabilities toward Job Satisfaction and Organizational Commitment: A Comparative Study of Indonesia vs Hong Kong - Indrajaya, Amelia Naim; Daryanto, Wiwiek M.; Zahirsyah, Rifa; Yeung, Shirley (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this research is to analyse the difference between the concept of spirit at work and spiritual leadership toward organizational commitment and job satisfaction in different cultural background of Indonesia vs Hong Kong. The research of spirit at work is a growing research, nevertheless more quantitative study is needed to support this topic. This study takes an empirical examination with 295 data taken from the online questionnaire through Google Form in Indonesia and 52 data from Hong Kong. The research shows the impact of organizational intangible resource (in the form of integrated spiritual leadership (SL) variables: Vision, hope/faith, altruistic love, meaning/calling and membership) toward SW, showing that SL is organized into employees experiencing SW. Further, SW is tested toward Job Satisfaction (JS) and Organizational Commitment (OC) as competitive advantages toward performance. Findings show different result of Indonesia vs Hong Kong. Further qualitative studies would be needed to support future findings.